Neuroendocrine tumor of parapharyngeal space - Adham, Marlinda; Widayanti, Novra (PERHATI-KL, 2013)
Background: Parapharyngeal space tumors account for some 0.5% of tumors of the head and neck, most ofthem benign. The most common benign neoplasms are salivary gland neoplasm, paragangliomas and followed byneurogenic tumors. The importance of these tumors lies mainly in two aspects, the difficulty of early diagnosis,due to the lack of symptoms in the initial stages and, on the other hand, the extreme risk of complications inperforming surgery in the parapharyngeal region. Purpose: We present this case to enlighten generalpractitioners and also otorhinolaryngologist about diagnosis and management of parapharyngeal tumor. Case:One clinical case of neuroendocrine tumor in parapharyngeal space on a 37 years old man. Management: Thepatient underwent diagnosis procedure and extirpation of the tumor mass. Conclusion: Parapharyngeal tumor isone of head and neck tumors that has good prognosis, especially if diagnosed early and adequately treated.Keywords: neuroendocrine tumor, parapharyngeal space, benign tumor.ABSTRAKLatar belakang: Tumor parafaring meliputi sekitar 0,5% dari seluruh tumor kepala dan leher, sebagianbesar jinak. Tumor jinak yang paling sering adalah tumor kelenjar liur, paraganglioma dan tumor neurogenik.Tumor parafaring ini penting disebabkan sulit untuk melakukan diagnosis dini karena sedikitnya gejala padatahap awal dan kemungkinan komplikasi yang dapat terjadi pada saat dilakukan tindakan bedah di daerahparafaring. Tujuan: Kasus ini diajukan agar para dokter umum dan spesialis Telinga Hidung Tenggorok dapatmengenali diagnosis dan penatalaksanaan tumor parafaring. Kasus: Dilaporkan satu kasus tumorneuroendokrin parafaring pada laki-laki usia 37 tahun. Penatalaksanaan: Pada pasien ini dilakukan proseduruntuk mendiagnosis tumor dan dilakukan ekstirpasi massa tumor. Kesimpulan: Tumor parafaring merupakansalah satu dari tumor kepala dan leher yang mempunyai prognosis baik terutama bila didiagnosis secara dinidan diterapi secara adekuat.Kata kunci: Tumor neuroendokrin, spatium parafaring, tumor jinak.